2020
DOI: 10.3390/horticulturae6020036
|View full text |Cite
|
Sign up to set email alerts
|

Plant Extract Treatments Induce Resistance to Bacterial Spot by Tomato Plants for a Sustainable System

Abstract: The aim of this study is to assess the effect of extracts of Nerium oleander, Eucalyptus chamadulonsis and Citrullus colocynthis against bacterial spot disease of tomato and to investigate the induction of resistance by tomato (Solanum lycopersicum) in order to promote a sustainable management system. The antibacterial activity of aqueous and ethanol plant extracts was tested against Xanthomonas axonopodis pv. vesicatoria, isolate PHYXV3, in vitro and in vivo. The highest antibacterial activity in vitro was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Defense-related enzymes such as peroxidase and polyphenol oxidase are mentioned as the plant induced systemic resistance (ISR) that correlates with disease control. These enzymes produced by the biosynthesis of plant metabolites, such as phenolic compounds, flavonoids, tannins and lignin [47,48], play an important role in plant stress tolerance, especially on fungal, bacterial and viral pathogens [49,50]. Many studies have indicated that the increase of defense-related enzymes activity due to greater accumulation of phenolic compounds can offer protection against plant diseases [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Defense-related enzymes such as peroxidase and polyphenol oxidase are mentioned as the plant induced systemic resistance (ISR) that correlates with disease control. These enzymes produced by the biosynthesis of plant metabolites, such as phenolic compounds, flavonoids, tannins and lignin [47,48], play an important role in plant stress tolerance, especially on fungal, bacterial and viral pathogens [49,50]. Many studies have indicated that the increase of defense-related enzymes activity due to greater accumulation of phenolic compounds can offer protection against plant diseases [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…At 3–4 leaf stage, seedlings were transplanted to new identical pots that were placed in greenhouse of the Department of Agriculture, Assiut University, Egypt. To fulfill the nutrient requirements, slow release fertilizer NPK (12:4:6) was added into soil [ 24 ]. The optimal temperature (30 ± 2 °C) and relative humidity (68–80%) inside the greenhouse was maintained and plants were irrigated as per requirement.…”
Section: Methodsmentioning
confidence: 99%
“…Leaf tissue (1 g) collected at the third leaf stage (14 DPS) was homogenized in 5 ml of 0.05 M phosphate buffer (pH 7.0) containing 10% polyvinylpyrrolidone (PVP-SIGMA) and 0.1 M ethylene di-amine-tetra-acetic acid (EDTA-SIGMA) and centrifuged at 14,000 rpm for 20 min at 4°C. POD activity was measured by the method of Abo-Elyousr et al (2020) . The assay mixture contained 0.1 ml enzyme extract, 1.35 ml 0.1 M mM MES buffer (pH 5.5), 0.05% H 2 O 2 , and 0.1% phenylenediamine.…”
Section: Methodsmentioning
confidence: 99%